PENGUATAN KAPASITAS KEBERDAYAAN MASYARAKAT DESA ADAT SIBETAN MELALUI PENYUSUNAN DETAILED ENGINEERING DESIGN PENATAAN PURA KEJU BERBASIS PERANCANGAN PARTISIPATIF - Prabawa, Made Suryanatha; Pratiwi, Made Widya; Laksmi, Ida Ayu Cri Vinantya; Salengko, Maribeth Glory Angel Prima; Putra, I Putu Eric Anantha (Universitas Kadiri, 2025)
The Keju Temple in Sibetan Traditional Village, Karangasem, Bali, was damaged by the 2021 earthquake, requiring technical documentation for the revitalization process. This Community Service (PkM) activity aims to prepare a Detailed Engineering Design (DED) for the arrangement of the Keju Temple using a participatory architectural approach that combines modern technical standards (SNI 1726:2019, SNI 1727:2020, PUIL 2011) with Balinese local wisdom (Asta Kosala Kosali, Tri Mandala, Tri Angga). The implementation method is carried out through five stages: socialization, training, DED preparation, FGD, and evaluation. The results of the activity are hard products (Architectural, Structural, and MEP DEDs) and soft products (increased community knowledge about technical documents and grant flows). The knowledge test showed an average increase of 40 points from the pre-test to the post-test, confirming the success of technology transfer. This activity has a double impact: tangible benefits for the community in the form of DED documents ready to be submitted for development grants, as well as academic productivity for universities through publications, IPR, and dissemination.